1994
DOI: 10.1007/bf02540463
|View full text |Cite
|
Sign up to set email alerts
|

A novel technique for the preparation of secondary fatty amides

Abstract: A low‐temperature synthesis of fatty alkanolamides, fatty diamides and fatty aralkylamides directly from triglycerides and primary amines provides essentially quantitative yields of the various products. The reactions run to completion in 3–12 h at temperatures of 50–60°C, approximately 100°C lower than employed in present conventional practice. The amines are used in excess and serve as solvent, reagent and, perhaps, as catalyst. The amides were characterized by melting point and spectroscopic (infrared and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 5 publications
0
31
0
1
Order By: Relevance
“…After reaching ambient temperature the seeds were transferred to boxes for storage before preparation of the ration. Fatty acyl amides of CO were prepared by reacting CO and ethanolamine (1.38 g oil/g ethanolamine) at 708C for at least 48 h according to the method described by Feairheller et al (1994).…”
Section: Feed Preparation and Animal Managementmentioning
confidence: 99%
“…After reaching ambient temperature the seeds were transferred to boxes for storage before preparation of the ration. Fatty acyl amides of CO were prepared by reacting CO and ethanolamine (1.38 g oil/g ethanolamine) at 708C for at least 48 h according to the method described by Feairheller et al (1994).…”
Section: Feed Preparation and Animal Managementmentioning
confidence: 99%
“…The amine was used in 1:4 molar ratios excess, the reagent was used as a solvent for HCO, and the formed fatty amide was used as the basic catalyst for the reaction. The excess amine prevented the reaction mixture from solidifying and permitted the completion of the reaction 17 . In this study, the molar ratio 1:4 was selected for further reaction.…”
Section: Wax Cardboard Coating Analysismentioning
confidence: 99%
“…In addition, the 3,500-3,300 cm 1 spectral region became a large board band because of the amide second overtone region. The ester peak can be used as an indicator of the extent of the completion of the reaction 17 . Figure 4 confirmed that the product was HCO fatty amide.…”
Section: Ftir Analysis Of the Nal Productmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatty alkanolamides, namely monoalkanolamide and dialkanolamide can be prepared by reacting fatty acids or fatty acid methyl esters with alkanolamine, such as monoalkanolamine or dialkanolamine at elevated temperature [1] . Lately, secondary fatty amides, such as alkanolamides have been reported to be synthesized by using triacylglycerides from tallow and tripalmitin to react with amine, such as ethanolamine, diethanolamine, ethylenediamine, diethylenediamine and others [2] . Besides, preparation of the ethanolamides by using laurel oil from black olive-sized fruits of Laurus nabilis L. has also been reported [3] .…”
Section: Introductionmentioning
confidence: 99%